The INFLUENCE OF WEBSITE CAPABILITY, SERVICE PERFORMANCE, AND E-WOM ON STUDENTS PURCHASE DECISIONS ON MARKETPLACE IN PONTIANAK CITY - Khurnadi, Vicky; Graceallah, Georgerius (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to examine the relationship between the variables of website capability, service performance, and electronic word of mouth (E-Wom) on students' purchase decisions on the marketplace in Pontianak City, this study uses a quantitative approach with three independent variables, namely website capability, service performance, and e-Wom, as well as one independent variable, namely purchase decision. The population in the study is marketplace users in Pontianak City, with a sample of 124 students determined through nonprobability sampling with accidental sampling techniques and collected through questionnaires. The results of the study show that: (1) website capabilities have a positive and significant effect on purchasing decisions, which confirms that reliable and effective website quality is able to influence students' purchasing decisions; (2) Service performance has a positive and significant effect on purchase decisions, so that service according to consumer expectations is able to increase purchases; and (3) e-WOM has a positive and significant influence on purchasing decisions, which means that a good review can influence a person to buy an item. These findings confirm the importance of website capabilities, service performance, and e-WOM as a way to improve purchasing decisions.